Systems Thinking in Workplace Health and Safety: A theory and Practice Nexus - Monyei, Francis Ezieshi; Arachie, Augustine Ebuka; Ukpere, Wilfred; Adekanmbi, Foluso (Annals of Spiru Haret University. Economic Series, 2024)
This paper undertakes a conceptual overview of system thinking in workplace safety and health with the intent of bridging the gap between theory and practice. It is based on the premise that there has been so much discussed in theory with very little to practice, that is making the modern workplace more hazardous and challenging. This study relied on existing literature and based on the frame an emerging economy perspective was articulated and discussed. The paper draws from a narrative qualitative approach design. The study concludes that there is more to be done in practice when it comes to workplace health and safety. The reality that modern workplaces evolve from a system view thus demands a holistic approach to viewing workplace safety and health, as it remains foundational to employee retention and effective contribution to the survival of the workplace.